2014
DOI: 10.1155/2014/591714
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Bone Osteomyelitis: The Relationship with Malignant Otitis Externa, the Diagnostic Dilemma, and Changing Trends

Abstract: Fifty-five patients hospitalized for osteomyelitis of the temporal bone between 1990 and 2011 were divided into two study groups: group 1 was patients collected from 1990 to 2001 and group 2 was composed of patients between 2002 and 2011. Clinical diagnostic criteria and epidemiologic data were analyzed to illustrate the altering features of osteomyelitis of the temporal bone. Group 1 patients were characterized by high prevalence of diabetes and more commonly suffered from otalgia, otitis externa and granulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
1
18
0
2
Order By: Relevance
“…SBO commonly occurs as a complication of MOE and chronic mastoid infections or secondary to sphenoidal sinusitis. [ 29 30 31 ] MOE primarily affects the temporal bone and is the most frequent cause of SBO. [ 31 ] A large study at the University of California Irvine from 1990 to 2000 reported a male-to-female ratio of 1:1 in 820 patients with SBO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SBO commonly occurs as a complication of MOE and chronic mastoid infections or secondary to sphenoidal sinusitis. [ 29 30 31 ] MOE primarily affects the temporal bone and is the most frequent cause of SBO. [ 31 ] A large study at the University of California Irvine from 1990 to 2000 reported a male-to-female ratio of 1:1 in 820 patients with SBO.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 30 31 ] MOE primarily affects the temporal bone and is the most frequent cause of SBO. [ 31 ] A large study at the University of California Irvine from 1990 to 2000 reported a male-to-female ratio of 1:1 in 820 patients with SBO. [ 32 ] The researchers reported the overall incidence of SBO as 69.3% in whites, 13.2% in Native Americans, 6.5% in African Americans, and 2.9% in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…The skull base inflammations described in the literature most often affect diabetic or immunodeficient patients [2, 1719]. Diabetics are more prone to skull base osteomyelitis [3, 810, 17, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…At the first examination, ESR levels were found to be increased by 50%-80% and CRP levels by 66.7%-78.6% in our study. As a result, ESR and CRP may be useful laboratory markers for the screening of MOE (20).…”
Section: Discussionmentioning
confidence: 99%